Frequency of obsessive-compulsive disorder in schizophrenic patients according to structural clinical interview (SCID) - Pakravan M; Ghalebandi MF; Alavi K; Afkham Ebrahimi A (مجله دانشگاه علوم پزشکی گرگان, 2007)
Background&Objective: The life time prevalence of schizophrenia is estimated about 1%-1.5% in United States and various studies have shown that between 7.8-46.6% of these patients suffer from OCD. The differences in these statistics are partly due to the assessment and treatment methods. The purpose of this study was to measure the frequency of OCD in hospitalized schizophrenic patients. Materials&Methods: The study was cross-sectional. 96 inpatients (56 men and 40 women) with DSM-IV schizophrenia diagnostic criteria were selected from Iran Psychiatry Hospital by simple non-random sampling Results: The age range of the patients were 17-73 with a mean age of 35 ±12.6. The majority of patients (88.5%) suffered from paranoid schizophrenia. 47 patients (49%) were diagnosed to have obsessive-compulsive symptoms on interview. The mean age of schizophrenia onset was 24.7 ±8.8 and the mean age of OCD onset in schizophrenic patients was 20.2 ±6.7. In 8 (17%), the two disorders were began simultaneously and in 20 (20.8%), schizophrenia was started earlier. Conclusion: Obsessive-compulsive symptoms are completely prevalent in schizophrenia. The co morbidity of these two clinical entities has both etiological and therapeutic importance.